Las manifestaciones gráficas prehistóricas en el dolmen de Soto (Trigueros, Huelva) - Garcês, Sara, (Archaeopress Archaeology, 2022)
Engraved and painted images upon the upright stones of the Dolmen de Soto were investigated and recorded by a team of international scientists using a variety of photogrammetric methods in 2016-17. This book tells the fascinating story of the archaeological and historical context of the site and presents the stunning results the project yielded.